Somatic instability of CTG repeat in myotonic dystrophy - Ashizawa, T; Dubel, J R; Harati, Y (Neurology, 1993)
An unstable expansion of the CTG repeat in the 3' untranslated region of the myotonin protein kinase (MT-PK) gene is the mutation specific for myotonic dystrophy (DM). To examine somatic stability of the repeat, we studied tissue variability of the repeat size. In five DM patients, the restriction fragment containing the repeat region was substantially larger in skeletal muscle than in peripheral blood leukocytes (PBL). In addition, one normal subject showed a size discrepancy in one of the normal alleles by one repeat on the polymerase chain reaction analysis. In most DM patients, the repeat size of native PBL differed from the transformed lymphoblastoid cells after passages. In contrast, various tissues from a congenital DM patient showed a similar size of the expanded repeat, including the transformed lymphoblastoid cells. We conclude that somatic instability of the CTG repeat may cause substantial tissue variability of the CTG repeat size in adult-onset DM, providing a potential mechanism for the variable pleiotropism.